The procedures before the universal bodies for the protection of human rights – current issues and perspectives - Tubić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
This paper deals with the issue of activities of international committees for the protection of human rights, which are created by universal treaties for the protection of human rights, such as International Covenant on civil and Political Rights, Convention Against Torture, Convention on the Elimination of All Forms of Racial Discrimination and other. The committees have jurisdiction to consider reports of the State Parties on the implementation of a relevant international treaty by which they were created. Also, the procedures of inter-state and individual communications are significant. Certain conditions of the admissibility of a communication, which are almost identical for every committee, should be fulfilled. Before initiating an international procedure State Party has the opportunity to remedy all the negative consequences that were caused by the violation of human rights and for that reason all available national legal remedies should be used. Also, the communications have to be compatible with the relevant convention, which means that individual has to address the right envisaged by the convention. In the procedures before a committee, the facts are investigated and the committee gives a decision or the opinion whether certain human right had been violated. During the procedure interim measures could be ordered to protect irreparable harm for the applicant. Decisions of the committees are not binding; however they influence a state to respect human rights of individuals in their jurisdiction. If the decisions are binding that would significantly contribute to the efficiency of the human rights protection before the committees. For that to happen, there should be explicit consent of the State Parties and the treaties, by which they are created, should be modified.